Navigating Economic Growth: An Analysis of Indonesia’s Maritime Axis Policy Implementation - Fikri Kamil Arizza; Guntur Eko Saputro; Zainal Abiddin Sahabuddin (PPSDP International Journal of Education, 2026)
This study aims to analyze maritime axis policies from the perspective of defense economics and policy implementation in order to grow Indonesia’s economy. Utilizing qualitative research approach, data was collected from a variety of sources, including academic journals, policy documents, and credible reports. The findings indicate that Indonesia’s Position as a maritime country, Indonesia has opportunities for economic growth and security as a national pillar. Indonesia’s maritime future is realized through synergy between communication, resources, and bureaucracy. economic development in enhancing economic growth is realized through the “Maritime Silk Road” and efforts to create harmony between the three aspects of policy implementation theory. However, challenges such as unsustainable practices, stakeholder conflicts, and inadequate policy coordination hinder effective implementation. The success of the maritime axis policy in Indonesia necessitates comprehensive implementation that integrate sustainability principles across all sectors, as well as collaboration among stakeholders. This finding provides valuable insights for policymakers in formulating policy implementation that promote sustainable development in maritime axis policy, ensuring that economic growth benefits can be enjoyed by both current and future generations. Thus, the maritime axis policy not only has potential to drive economic growth but also safeguard in marine ecosystems that are essential for the livehood of coastal communities. From that we may know maritime policy can drive economic development by focusing on infrastructure development, natural resource and human resource management, maritime improvement, and international cooperation.